EU multi-level trade policy: Neither coherent nor development-friendly - Birgit Mahnkopf (International Labour Organization (ILO), 2008)
In this paper, we will endeavour to explain why EU trade politics is neither coherent with its development policy nor development-friendly. This becomes even more obvious when one looks at the numerous bilateral trade agreements already signed and still in the process of negotiation. While the EU views itself as a true believer in multilateral policy, it succeeded to negotiate more Preferential Trade Agreements than the US. Against this background it is to be shown in the following that Preferential Trade Agreements (PTA) including Bilateral Investment Treaties (BIT) deserves more attention, and that the new trade strategy of the European Community is mimicking the prevalent US approach to trade politics, and thus should come under attack from trade unions and civil society movements. Finally, this paper argues that although in principle PTAs can include labour-friendly provisions more easily than at the WTO level, trade unions' more ambivalent attitude towards PTAs is justified. However, from a development point of view, trade unions from the industrialized countries need to change their reluctance towards a fundamental criticism of ongoing trade policy, be it US or European type.
Keywords: 330